THE PRINCIPLE MANAGEMENT IN IMPROVING TEACHER PROFESSIONAL AT STATE ISLAMIC MODEL SENIOR HIGH SCHOOLOF BANDA ACEH AND STATE SENIOR HIGH SCHOOL ABULYATAMA OF ACEH BESAR - Rasyid, Suparta (Universitas Pendidikan Indonesia, 2022)
Implementation of leadership in improving teacher professionals, and principal programs which is very important to do especially in the principal program and the purpose of education it self. The purpose of this research is to know: the formulation of the program, the implementation of management, and the obstacles faced by the principal in running the management in improving the professional teacher. This research uses descriptive method with qualitative approach. Data collection techniques: observation, interview, and documentation study. The subjects of this study were principals, vice principals, teachers, MGMP, school committees, supervisors, and outstanding teachers. The results of this study indicate that: (1) The principal's program in improving teacher professionals, the formulation mechanism begins with deliberations between stakeholders as well as principals, Chair of the MGMP, School committees, supervisors, and outstanding teachers. Prepared programs, long-term, medium and short-term programs, and all these programs are guided by the provincial government of Aceh. All of this is already in the principal's management as embodied in the principal's program to improve teacher professionalism. (2) the principal conducts the principal's management to improve the teacher's professionalism by applying subordinates and principals taking approaches to improve teacher professionalism. For teachers who excel in the form of promoting the name of the teacher to follow CAKEP, and promoted. (3) the obstacles faced by the principal in improving teacher professionals to find teachers who are still less than the maximum in the work or the teacher is less concerned about the situation at school.